Amazon deforestation restrictions likely to be circumvented - Ribeiro, Ricardo da Silva; Vicente, Ricardo Eduardo; Arrolho, Solange; Fearnside, Philip M. (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
Brazil’s state of Mato Grosso is part of the “Legal Amazon” region where deforestation is limited by a requirement in the country’s Forest Code, which specifies that 80% of each property must be maintained in native vegetation in areas that were originally Amazon Forest and 35% in areas that were originally Cerrado (central Brazilian savanna). A new bill (PL 377/2022) that is rapidly advancing in the National Congress would remove Mato Grosso from the Legal Amazon, reducing this requirement to 20% in both cases.